The Impact of Interventions to Improve Sleep on Delirium in the ICU: A Systematic Review and Research Framework*. Issue 12 (December 2016) - Flannery, Alexander H.; Oyler, Douglas R.; Weinhouse, Gerald L.
Abstract : Objective: This study aimed to assess whether interventions targeted at improving sleep in the ICU were associated with reductions in ICU delirium. Secondary outcomes include duration of delirium and ICU length of stay. Data Sources: MEDLINE, CINAHL, Web of Science, Scopus, WorldCat, and International Pharmaceutical Abstracts were searched from inception to January 2016. Study Selection: Studies investigating any type of sleep intervention (nonpharmacologic or pharmacologic) and assessing the impact on ICU delirium were included. Any type of study design was permitted so long as the delirium assessment was made at least daily with a validated delirium assessment tool. Data Extraction: The following data were extracted: first author, year of publication, study design, ICU type, components of sleep intervention, use of sleep assessment tool, patient age, sex, severity of illness, sleep measures, delirium assessment tool, incidence of delirium, duration of delirium, and ICU length of stay. The incidence of delirium was used to compare rates of ICU delirium across studies. Methodologic quality of included studies was evaluated using the Effective Public Health Practice Project quality assessment tool. Data Synthesis: Of 488 citations screened, 10 studies were identified for inclusion in the final review; six of which demonstrated a statistically significant reduction in the incidence of ICU delirium associated with sleep intervention. Four studies assessed duration of delirium; of which, three reported a shorter duration of delirium with sleep intervention. Two studies associated sleep intervention with a reduced ICU length of stay. In regard to quality assessment and risk of bias, only one study was assessed as strong. Multiple identified confounders and the significant qualitative assessment of heterogeneity limit both the conclusions that can be drawn from these findings and the quantitative pooling of data. Conclusions: Although sleep interventions seem to be a promising approach for improving delirium-related outcomes, studies are limited by bias issues, varying methodologies, and multiple confounders, making the evidence base for this conclusion limited at best. Future studies would benefit from a systematic approach to studying the link between sleep intervention and delirium-related outcomes, which is outlined in the context of reviewing the existing literature. Abstract : Supplemental Digital Content is available in the text.